Study on the effect of impact force in copra separation - ATHUL CHANDRAN K SANU K.A VISHNU SANKAR A; Er. Shivaji K.P (Guide) (Tavanur 2015 Department Of Farm Power Machinery and Energy)
Study on the effect of impact force in copra separation
Study on the effect of impact force in copra separation